Administrative Wage and Labor Market Flow Panel (AWFP) 1975-2014 - Stefan Seth; Heiko Stüber (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2017)
This paper describes the new Administrative Wage and Labor Market Flow Panel (AWFP). The AWFP is a dataset on labor market flows and stocks for the universe of German estab-lishments. It contains data on job flows, worker flows, and about wages for each establishment. The AWFP contains this information also for partitions of the labor force according to various employee characteristics and for some subgroups of employees. The AWFP covers the time period 1975-2014. All data are available at an annual and quarterly frequency.
Is replaced by the following version: http://hdl.handle.net/10419/189829
Keywords: 330; establishment data; job flows; worker flows; wages; German administrative data